Plans of the German Government to Reform the Law of Guardianship for Minors: A presentation of the present and the future law in Germany - Oberloskamp, Helga (LeXonomica, 2017)
For years the praxis has asked for a new law of guardianship, because many things in the current law (which is 117 years old) do not cover the needs of today. Although no one wants to abandon the German system of hav-ing single persons, private organizations and public institutions being guardians, it is disputed until today if there is a ranking between them and if it should be possible to give several guarding/ educating persons to one child and if yes who should bear responsibility. Besides a new law should express clearly the rights of the children and the responsibilities of the guardians.